2018
DOI: 10.1001/jamadermatol.2017.5937
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Guselkumab, an Anti–interleukin 23 Monoclonal Antibody, for Palmoplantar Pustulosis

Abstract: IMPORTANCE Palmoplantar pustulosis (PPP) is a recalcitrant skin disease with no biologics currently approved for treatment. The involvement of interleukin 23 (IL-23) and cytokines of the type 17 helper T cell lineage in the pathogenesis of PPP has been recently postulated. OBJECTIVE To evaluate the efficacy and safety of guselkumab, an anti-IL-23 monoclonal antibody, in Japanese patients with PPP. DESIGN, SETTING, AND PARTICIPANTS This double-blind, randomized, placebo-controlled, parallel-group, 24-week trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
111
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(125 citation statements)
references
References 35 publications
7
111
1
1
Order By: Relevance
“…There were no deaths, injection‐site reactions, anti‐guselkumab antibodies or serious infections reported in the study. The overall safety results of this study in Japanese patients treated with guselkumab were consistent with the previous studies conducted in a global population with moderate to severe plaque psoriasis and in Japanese patients with moderate to severe psoriasis and palmoplantar pustulosis …”
Section: Discussionmentioning
confidence: 99%
“…There were no deaths, injection‐site reactions, anti‐guselkumab antibodies or serious infections reported in the study. The overall safety results of this study in Japanese patients treated with guselkumab were consistent with the previous studies conducted in a global population with moderate to severe plaque psoriasis and in Japanese patients with moderate to severe psoriasis and palmoplantar pustulosis …”
Section: Discussionmentioning
confidence: 99%
“…In a recent study of 49 patients conducted by Terui et al in 2018, guselkumab was used to treat palmoplantar pustulosis. Onset of clinical response within 2 weeks of therapy with a trend toward improvement until week 24 (Terui et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…By antagonizing IL-23p19, this inflammatory pathway is disrupted and therefore is a viable biological therapy for these immune-mediated skin conditions. In a recent study of 49 patients conducted by Terui et al in 2018, guselkumab was used to treat palmoplantar pustulosis. Onset of clinical response within 2 weeks of therapy with a trend toward improvement until week 24 (Terui et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In PPP skin lesions, the CCL20–CCR6 axis may contribute to a positive feedback loop involving the recruitment and migration of effector Th17 cells, as well as the amplification of inflammation and tissue destruction. This speculation was supported by the favorable outcome in a clinical trial using secukinumab (anti‐IL‐17A antibody) or guselkumab (anti‐IL‐23 antibody) for PPP patients; however, the limited efficacy showed that other factors were also involved in PPP pathogenesis …”
Section: Pathogenic Role Of Tonsils In Pppmentioning
confidence: 99%